Strontium Regulates the Proliferation and Differentiation of Isolated Primary Bovine Chondrocytes via the TGFβ/SMAD Pathway - Liu, Siqi; Shen, Bingyu; Loor, Juan J.; Jiang, Qianming; Yuan, Yang; Kong, Yezi; Tan, Panpan; Zeng, Fangyuan; Zhao, Chenxu; Zhu, Xiaoyan; Wang, Jianguo (Frontiers in Pharmacology, 2022)
The present study evaluated the effects of strontium (Sr) on proliferation and differentiation of chondrocytes isolated from dairy cows, and whether Sr exerts its effects via transforming growth factor β (TGFβ) signaling. The chondrocytes were isolated from patellar cartilage from newborn Holstein bull calves (n = 3, 1 d old, 38.0 ± 2.8 kg, fasting) within 15 min after euthanasia, and treated with different concentrations of Sr (0, 0.1, 1, and 10 μg/mL, as SrCl2·6H2O). After pretreatment with or without activin receptor-like kinase 5 (ALK5) inhibitor (10 μM SB-505124) for 4 h, chondrocytes were incubated with Sr for another 4 h. Overall effects of Sr were evaluated relative to NaCl as the control. In contrast, the 1 μg/mL Sr-treated group served as the control to determine effects of preincubating with SB-505124. Western blot and qRT-PCR were used for measuring expression of proliferation-, differentiation-, and TGFβ1-responsive factors. Data were analyzed using one-way ANOVA in GraphPad Prism 7.0. Incubation with all doses of Sr increased TGFβ1/ALK5-induced SMAD3 phosphorylation, and at 10 μg/mL it inhibited ALK1-induced SMAD1/5/9 phosphorylation. Expression of mRNA and protein of the proliferation-responsive factors type Ⅱ Collagen α1 (COL2A1) and aggrecan (ACAN) was induced by Sr at 1 μg/mL. In contrast, Sr at 10 μg/mL inhibited the expression of differentiation-responsive factors type Ⅹ Collagen α1 (COL10A1) and secreted phosphoprotein 1 (SPP1), and at 1 μg/mL it had the same effect on alkaline phosphatase (ALPL) mRNA and protein levels. Cells were stained with PI/RNase Staining buffer to assess cell cycle activity using flow-cytometry. Incubation with Sr at 1 and 10 μg/mL induced an increase in the number of cells in the S-phase, leading to an increase in the proliferation index. Incubation with SB-505124 inhibited phosphorylation of SMAD3. Abundance of ACAN and COL2A1 mRNA and protein was lower when cells were pre-incubated with SB-505124. Overall, data indicated that Sr promotes proliferation and inhibits differentiation of primary chondrocytes by directing TGFβ1 signaling towards SMAD3 phosphorylation rather than SMAD1/5/9 phosphorylation. Whether these effects occur in vivo remains to be determined and could impact future application of Sr as an experimental tool in livestock.